Physicochemical, mechanical and thermal properties of twisted ramie (Boehmeria Nivea) fibers for their potential use as reinforcement in non-structural concrete - Maidina Maidina; Fadhilah Muslim; Fitriani Fitriani; Agung Sumarno; Ismail Budiman; Gabriel Andari Kristanto; Fauzi Hardjanto; Heru Purnomo (Case Studies in Chemical and Environmental Engineering)
This study examines the use of 3 ply twisted Ramie (Boehmeria Nivea) fibers as reinforcement in non-structural concrete. The physicochemical, mechanical, and thermal properties of the fibers were assessed at 7, 14, and 28 days after embedding in concrete. The fibers are mainly composed of cellulose. Microstructure analysis reveals hydration products such as Ca(OH)2, C–S–H, and Ca(CO)3. At 28 days, tensile strength decreased by 8.72 %, and thermal resistance (250°C -400 °C) was lower than the hydration temperature. Hydrophilic behavior was evident at 7 and 14 days. These findings suggest twisted ramie fibers could serve as an eco-friendly reinforcement alternative in non-structural concrete.